(untitled) (IJM: Journal of Multidisiplinary, 2025)
This study aims to identify and analyze the impact of product quality, price, and product innovation on customer loyalty among iPhone users in the East Bekasi area. The research adopts a quantitative approach using a survey method, where data was collected through questionnaires distributed to 102 respondents who are iPhone users in East Bekasi. A purposive sampling technique was used to select samples that meet the specific characteristics required for this study. Data analysis was conducted using multiple linear regression with SPSS version 25 software to test the effect of each variable on customer loyalty. The analysis results show that, partially, product quality, price, and product innovation have a positive and significant effect on customer loyalty. The regression results indicate that all three variables together have a significant impact on the customer loyalty of iPhone users. These findings emphasize that customers tend to be more loyal to the iPhone brand when the product quality offered is high, the price is perceived as fair in relation to the value received, and the product innovations meet their expectations and needs. This study provides valuable insights for technology companies, especially Apple, to enhance customer loyalty.